IMPLEMENTASI KEBIJAKAN TAMBAHAN PENGHASILAN PEGAWAI DI BIRO UMUM SEKRETARIAT DAERAH SULAWESI TENGAH - Perwira, Ryan (Katalogis, 2015)
This Research Aim To Find Out Implementation Of Officers’ Extra Policy And Implication Of Extra Income Toward Officers’ Working Motivation At Regional Secretariat General Bureau Of Central Sulawesi Province. Theory Used Is From Edward III Consisting Of Some Factors For Measuring Policy, Communication, Resources, Bureaucratic Structure, And Disposition. This Research Type Is Qualitative. The Informants Are The Officers’ Of Regional Secretariat General Bureau Of Central Sulawesi Province. The Data Were Collected Through Observation, Interview And Documentation. The Technique Of Data Analysis Covers Data Reduction, Data Display, And Drawing Conclusion. The Research Result Indicates That The Implementation Of Officers’ Extra Income Policy And Implication Of Extra Income Toward Officers’ Working Motivation At Regional Secretariat General Bureau Of Central Sulawesi Province Has Not Fully Been Good Because From The Aspect Observed There Was A Factor Did Not Support, Thar Was Resources While The Other Factors Were Already Good.